2010
DOI: 10.4137/mbi.s3822
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Control of Flour-Manufacture: Dissemination of Mycotoxins Producing Fungi in Cereal Products

Abstract: Wheat grain and its products are widely consumed as fodder and basic daily food stuffs in Kyrgyzstan. Mycobiota is known to produce hazardous effects to a consumer since it produces mycotoxins. Henceforth, mycobiota starting from the field stage to flour, grain and flour samples were selected for mycological analysis from eight sites of flour manufacture: grain stored in storehouses before milling, mechanically cleaned grain, washed grain, grain dried and prepared for mill, roughly-milled flour, first grade fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 14 publications
(27 reference statements)
0
17
0
Order By: Relevance
“…The Petri dishes were incubated at 25 ± 2°C, in darkness and observations relating to fungal colonies growth on wheat seeds were visualized using stereo-binocular microscope. The number of contaminated seeds was used in order to estimate the seeds contamination index (SCI) according to Doolotkeldieva et al using the formula (1) [24]:…”
Section: Experimental Researchmentioning
confidence: 99%
“…The Petri dishes were incubated at 25 ± 2°C, in darkness and observations relating to fungal colonies growth on wheat seeds were visualized using stereo-binocular microscope. The number of contaminated seeds was used in order to estimate the seeds contamination index (SCI) according to Doolotkeldieva et al using the formula (1) [24]:…”
Section: Experimental Researchmentioning
confidence: 99%
“…Many other investigators have isolated similar species of fungi from wheat flour. Doolotkeldieva (2010) and Al-Dfiery and Merjan (2015) found that the major genera of molds isolated from wheat flour and stored wheat flour according to decreasing frequency were Aspergillus, Penicillium, Fusarium, Cladosporium, Alternaria, Mucor, Rhizobacteria, Trichoderma, Rhizopus, Nigrospora, Bipolaris and Macrophomina. It is worthy to mention that A. niger, A. mellus, A. nidulance, Cladosporium sphaerospermum, Emercilla quadrilianiata and Eurotium repens were only isolated from infested flour samples with insects. These fungi might be introduced through insects i.e., the insects act as vectors of these fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Agricultural products and their processed foods have a wide range of usage all over the world, and numerous studies have shown that many of them are contaminated by mycotoxigenic fungi and their mycotoxins . According to the FAO, at least 25–40% of cereals/cereal products consumed worldwide are contaminated with mycotoxins .…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Agricultural products and their processed foods have a wide range of usage all over the world, and numerous studies have shown that many of them are contaminated by mycotoxigenic fungi and their mycotoxins. 71 According to the FAO, at least 25-40% of cereals/cereal products consumed worldwide are contaminated with mycotoxins. 4,20 Among the many methods used for the determination of mycotoxin contamination, high-performance liquid chromatography (HPLC) is most useful in terms of specificity and sensitivity, especially with an immunoaffinity column R Demirel, NY Sariozlu clean-up step to concentrate and purify mycotoxins and a fluorescence detector to detect the fluorescence properties of mycotoxins.…”
Section: Introductionmentioning
confidence: 99%